Pembacaan Heuristik dan Hermeneutik Ferdinand De Saussure Symbol Ketimpangan Gender Dalam Novel Perempuan di Titik Nol - Tjalau, Cutri; Gazali, Indriani; Sarif, Suharia (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2023)
The novel is an imitation of the life of the society around it. Literary works such as novels are cultural products that hold value as a means of communication for conveying ideas in the form of texts or stories, providing thousands of meanings within, especially in discussing the reality of social life.